2021
DOI: 10.33003/fjs-2021-0502-522
|View full text |Cite
|
Sign up to set email alerts
|

Candida Diagnostic Platforms: Essential in Early Management of Candida Infections

Abstract: Invasive candidiasis (IC) is associated with high morbidity and mortality. Candida species have significant roles in invasive candidiasis andthe emergence of clinical strains that are difficult to treat due tovirulent and resistant properties. Expansion of fungal pathogen diversity necessitates the development and adoption of new methods for prompt diagnosis and management. The review aimed to highlight the relevance of different Candida diagnostic methods for prompt management of Candida infections. The conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The ITS 1 and ITS 2 are two vital non-coding regions composed of conservative and variable subregions outside and inside respectively [45]. The ITS1 fragment is positioned between the 18S and 5.8S ribosomal RNA genes while ITS2 fragment is positioned between 5.8S and 28S ribosomal RNA genes [48]. Furthermore, the amplicon sizes differ according to the target ITS1 region based on specific Candida species of interest [33,49].…”
Section: The Internal Transcribed Spacer Marker For Candida Species I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ITS 1 and ITS 2 are two vital non-coding regions composed of conservative and variable subregions outside and inside respectively [45]. The ITS1 fragment is positioned between the 18S and 5.8S ribosomal RNA genes while ITS2 fragment is positioned between 5.8S and 28S ribosomal RNA genes [48]. Furthermore, the amplicon sizes differ according to the target ITS1 region based on specific Candida species of interest [33,49].…”
Section: The Internal Transcribed Spacer Marker For Candida Species I...mentioning
confidence: 99%
“…Furthermore, the amplicon sizes differ according to the target ITS1 region based on specific Candida species of interest [33,49]. It is worth noting that ITS primer design, PCR amplification and sequencing has been made easy due to availability of several conserved sequences, frequent copies of the ribosomal operon and moderately limited length of ITS region [48].…”
Section: The Internal Transcribed Spacer Marker For Candida Species I...mentioning
confidence: 99%
“…Therefore, these properties cause cell aggregation that will be difficult to disperse. Moreover, a study on the draft genome of C. auris found that a significant portion of its genes is centrally designated for metabolism activities, thus suggesting its adaptation to different environments [22][23][24][25][26]. McCarty and Pappas [5] indicated that C. auris in an infected or colonized patient deeply contaminates the patient's surrounding, which may serve as a potential reservoir…”
Section: Nosocomial Outbreaks Rapid Rate Of Transmission and Mortalitymentioning
confidence: 99%
“…The four genetic loci which are commonly used in identifying C. auris include ITS1/2, D1/D2, or IGS1 and IGS2 because of their discriminatory properties in differentiating strains in the C. haemulonii complex and C. auris [72]. Internal transcribed spacer (ITS) regions, D1/D2 domain, and intergenic spacers of the fungal ribosomal DNA large subunit sequences are universal barcode markers for fungal detection, as shown in Figure 2 [22,24]. They also play an essential role in differentiating clades from different geographical locations, as observed in the study conducted in the United Kingdom using a specific and rapid PCR technique.…”
Section: Adoption Of Molecular-based Approaches For Diagnosismentioning
confidence: 99%
“…In addition to these techniques, DNA-based approaches also aid in the differentiation of distinct Candida spp. with high sensitivity and specificity 15 .…”
Section: Introductionmentioning
confidence: 99%